Innovation of Suminten Edan Stories by Ketoprak Wahyu Manggolo Pati - Purnomo, Sucipto Hadi; Astuti, Tri Marhaeni; Irianto, Agus Maladi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
This research aims at discovering the innovation performed by artists of people’s theatre to the stories which have been a tradition and commonly known to the audience. This research uses a qualitative-descriptive approach, focusing on the performance of Sumonten Edan (SE) story by a ketoprak group Wahyu Manggolo Pati. In performing the story, despite being bound by the basic norms of performance known as pakem, Suminten Edan story is performed with some modifications to show innovations. These innovations include both the story and performance aspects.